HSV encephalitis with normal initial CT scan - a case report with a review of the literature - Marcin Kulczyński; Małgorzata Abramczyk; Klaudia Sapko; Michał Marciniec; Przemysław Dyndor; Katarzyna Dyndor (Kazimierz Wielki University, 2020)
Introduction. HSV-1 is the most common cause of viral encephalitis with a high mortality rate if left untreated and causes frequent diagnostic difficulties. It commonly involves the temporal, inferior frontal lobes and the limbic system. HSV can be differentiated by a combination of symptoms, laboratory tests and neuroimaging findings. Case report. A 29-year old female with HSV encephalitis, who, despite prevailing symptoms of altered mental status, had no abnormalities on initial CT head scan. Three MRI follow-up examinations revealed imaging findings with characteristic evolution. Despite CSF results being negative for HSV antibodies, the combination of symptoms, CSF analysis, and characteristic MRI findings were highly suggestive to diagnosing HSV encephalitis and to implement proper treatment. Discussion. In case of radiological changes in temporal lobe, the involvement of the Herpes simplex encephalitis (HSE) should always be considered. Although the laboratory tests happen to be inconclusive or even falsely negative, neuroimaging often helps to determine the diagnosis. Despite HSE being a severe neurological disorder, initial CT scans can be normal. MRI has become superior, especially at the early phase of the disease and is capable of determining the extensiveness of lesions.